The impact of the creative environment on the creative person, process, and product - Garcês, Soraia (2021)
Creativity is a highly complex concept, studied through different perspectives and evaluated by numerous instruments. Despite its conceptual and methodological diversity, the Rhodes’ multidimensional theory continues to be one of the main references in the study of creativity. Based on this theory, this study intended to observe the impact of the creative environment on the creative person, process, and product through a sample of 215 college students. Results suggest a significant influence from the creative environment on the creative process and product. Participants from the social sciences and arts performed better on the creative process and product, respectively. No statistically significant interaction effects were found regarding gender and the creative environment. However, age presents a control effect over the relationship between the creative environment and the plastic arts. Practical and educative implications are discussed.